Photo-controllable percolation of decorated nanoparticles in a nanopore: molecular dynamics simulation study - Ilnytskyi, J. M.; Slyusarchuk, A. Y.; Saphiannikova, M. (Publishing House of Lviv Polytechnic National University, 2016)
By means of molecular dynamics simulations we study formation of the wall-to-wall percolation cluster in the solution of decorated nanoparticles in a pore. The model takes into account photo-switching between unpolar trans and polar cis-isomers of azobenzene. This leads to either colloidal dispersion of the particles or their aggregation in a polar solvent. The dynamics of percolation cluster formation is analysed by applying a pulse-like illumination. We found that the wall-to-wall percolation is subject to the competition between nanoparticles aggregation, wall adsorption and microphase separation of the nanoparticles. Використовуючи метод молекулярної динамiки дослiджено формування перколяцiйного кластера у розчинi декорованих наночастинок помiщених у пору. Модель враховує фото-перемикання мiж неполярними trans та полярними cis-iзомерами азобензину, що приводить до або колоїдної дисперсiї або агрегацiї наночастинок у полярному розчиннику. The model takes into account photo-switching between unpolar trans and polar cis-isomers Динамiка формування перколяцiйного кластера вивчена шляхом прикладення пульсуючого опромiнення. Знайдено що перколяцiя мiж стiнками пори залежить вiд конкуренцiх мiж такими механiзмами як: агрегацiя наночастинок, адсорбцiя наночастинок на стiнках пори та мiкрофазне розшарування.
Фотоконтрольована перколяцiя декорованих наночастинок у порi: комп’ютерна симуляцiя методом молекулярної динамiки
Keywords: gold nanoparticles; azobenzene; percolation; наночастинки золота; азобензин; перколяцiя